Is Ovarian Preservation Feasible in Early-Stage Adenocarcinoma of the Cervix? - Lu, Huaiwu (Med Sci Monit, 2016)
BACKGROUND: In cervical adenocarcinoma, surgical treatment involves bilateral oophorectomy, which affects the long-term quality of life. The aim of our study was to access the incidence of ovarian metastasis in early-stage cervical adenocarcinoma and to suggest an algorithm for the triage of these patients to preserve the ovaries. MATERIAL/METHODS: A total 101 patients with cervical adenocarcinoma who had undergone radical hysterectomy with pelvic lymphadenectomy and bilateral oophorectomy were included in this study. Data on the clinicopathologic characteristics of the cases were collected and low risk factors for ovarian metastasis in early-stage cervical adenocarcinoma were analyzed. RESULTS: The ovary metastasis rate of cervical adenocarcinoma in this study was 4.95%, while it is only 2% in stage IB1. Pathological grade, LSVI, lymph node status, tumor size, depth of stromal invasion, and involvement of the junction of the cervix and the body of the uterus were associated with ovarian metastasis, while LSVI, lymph node status, depth of stromal invasion, and involvement of the junction of the cervix and the body of the uterus were associated with ovarian metastasis in stage IB. Multivariate analysis revealed that LVSI and lymph node metastasis were independent risk factors for ovarian metastasis in all stages of cervical adenocarcinoma, but involvement of the junction of the cervix and the body of the uterus was an independent risk factor for ovarian metastasis in stage IB. CONCLUSIONS: The incidence of ovarian metastasis in cervical adenocarcinoma is low. Our study suggests that ovarian preservation is safe and feasible in patients with no risk factors for ovarian metastasis. Further prospective studies are warranted.